Immunosensor for the Diagnostics of Autoimmune Hemolytic Anemia (AIHA) Based on Immobilization of a Monoclonal Antibody on a Layer of Silk Fibroin - Moraes, Marli L.; Lima, Lais R. [UNESP]; Vicentini-Oliveira, Josy C. [UNESP]; Souza, Aparecida Vitoria G. de [UNESP]; Oliveira, Osvaldo N.; Deffune, Elenice [UNESP]; Ribeiro, Sidney J. L. [UNESP] (Amer Scientific Publishers, 2019)
The diagnostics of the autoimmune hemolytic anemia (AIHA), a rare disease caused by autoantibody-induced hemolysis, is still prone to false positives for it is based on visual observation in the so-called Direct Coombs test. In this study, we developed a specific IgG hemolysis immunosensor produced with layer-by-layer (LbL) films containing a monoclonal antibody against human immunoglobulin (mAbIMUG) deposited along with a layer of silk fibroin (SF) derived from Bombyx mori cocoons. Adsorption of mAbIMUG on a SF layer was confirmed by the fluorescence emission band at 326 nm. Immunosensors were prepared with LbL films deposited on interdigitated gold electrodes for impedance spectroscopy and on screen printed carbon electrodes for electrochemical measurements. When the SF/mAbIMUGLbL film was exposed to healthy red blood cells (RBCs), no cell binding was observed by the optical microscopy images. In addition, no major changes were observed in the signals of the square wave voltammogram and in the impedance spectra. In contrast, the electrochemical signal was significantly increased and the dielectric loss curve shifted for the sensing units containing RBCs with the antibody attached on the surface (sick cells). Furthermore, cell attachment was so strong that optical images still showed covered electrodes even after washing in PBS buffer. The detection with two distinct methods seems promising for an effective diagnosis of AIHA.
Keywords: Immunosensor; Layer-By-Layer Films; Monoclonal Antibody; Autoimmune Hemolytic Anemia